Environmental sustainability in the OECD: The power of digitalization, green innovation, renewable energy and financial development - Karlilar, Selin; Balcilar, Mehmet; Emir, Firat (Elsevier Sci Ltd, 2023)
Digitalization has emerged as a crucial factor in reducing pollution and holds significant potential for facilitating the transition to a low-carbon economy. Nevertheless, the environmental impact of digitalization hinges on the strategies for collaboration with various economic actors and, as a result, their engagement with digitalization. In light of this, the present study seeks to examine the externality effect of digitalization on green innovation, renewable energy, and financial development in relation to environmental sustainability. The analysis employs the System Generalized Method of Moments (SYS-GMM) for 36 OECD countries over the period of 2000-2018. The empirical findings indicate that digitalization, green innovation, renewable energy, and financial development substantially promote environmental sustainability. Moreover, the interaction between digitalization, green innovation, renewable energy utilization, and financial development enhances the ecological footprint-mitigating effect of digitalization. In view of these results, merging digitalization and environmental policies may yield more robust outcomes and improved environmental quality compared to implementing a single policy in isolation.
Keywords: Digitalization; Ecological footprint; Green innovation; Renewable energy; Financial development; OECD countries